PSEUDO-BEAUTY: SEXUALITY IN INDAH HANACO’S THE CURSE OF BEAUTY (A STUDY OF CRITICAL DISCOURSE ANALYSIS) - Farokhah, Fiqih Aisyatul; Habsari, Sri Kusumo; Mugijatna, Mugijatna (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2018)
This article uses critical discourse analysis to uncover the discourse of pseudo beauty included the shape of the discourse and the reaction of sales promotion girl (SPG) which is represented in Indah Hanaco’s novel The Curse of Beauty. The design of the research is descriptive qualitative. Women wear thick makeup and attractive dress to cover their weakness, and they can be considered as beautiful women. Makeup makes the face more real than the reality thus it is mentioned as pseudo beauty. It makes SPG tries hard to become beautiful and sexy as a way of attracting the consumers. Most of them are trapped in the world of prostitution as the facilitator of sex tourism. SPG and prostitution seemingly become a stereotype that cannot be separated. They are tormented by a falseness and loneliness life in the halfway of hedonism. Capitalism makes them do not have a choice except being SPG which is a side job in sex tourism. These situations are caused by the pseudo beauty which gives them the curse as like represented by Indah Hanaco in her novel The Curse of Beauty.